A Synthesis Report on Piloting of Remote Phone-Based Formative Assessment Solutions in Ghana, Nepal, and Pakistan - Khurana, Aishwarya; Levin, Victoria; Luna-Bazaldua, Diego; Liberman, Julia (World Bank, Washington, DC, 2022)
School closures related to Coronavirus disease 2019 (COVID-19) not only disrupted education but also impacted teachers’ ability to know whether and what their students were learning. This information gap was most challenging in contexts with limited internet connectivity and low access to smart digital devices. In such circumstances, conducting formative assessments remotely using basic phones was seen as a means to provide timely information to teachers, parents, and students and support learning continuity outside the classroom. As students return to school, the same solutions can be used to complement in-person instruction to accelerate learning recovery, expand the use of formative assessment in hard-to-reach schools, and improve the resilience of education systems when confronted by future shocks. This report describes the three pilot studies that aimed to test the logistical and technological feasibility of using short message service (SMS), interactive voice recording (IVR), and live phone calls (LPC) to conduct formative assessment of foundational math and literacy skills for primary-grade students. These pilot studies were conducted in Ghana, Nepal, and Pakistan between October 2020 and January 2022.